Identification of the Implementation of Environmental Sanitation in Settlements in Mataram District, West Nusa Tenggara - Ernawati, Ernawati; Rahayu, Rachmawati Noviana; Supardiono, Supardiono; Isrowati, Isrowati; Akbar, Cahyo Aditya; Saputra, Kurniawan Adi; Wahyuni, Elisa Darmasari; Putra, Hengki Adriyan; Hidayati, Cita Rizqi (Jurnal Pijar Mipa, 2024)
Sanitation is an important health initiative that protects the cleanliness of the environment and its users. Basic sanitary facilities include clean water, wastewater treatment, drainage channels, and waste management. This research aims to provide an overview and information regarding the availability of basic sanitation facilities in a settlement. The research was conducted in Mataram District, West Nusa Tenggara. The research method used in this research is a descriptive qualitative method. The research focuses on identifying fundamental sanitation aspects, which include design and construction, waste management, wastewater management, and drainage systems. Direct observation, structured interviews, and in-depth interviews gathered data. According to the research findings, Mataram District's clean water supply comes from PDAM and drilled wells; waste management is not optimal because waste sorting and processing are not yet available, wastewater treatment is still done on-site in septic tanks in each house, and some wastewater comes from washing activities. While bathing drains into the gutter, the residents' yards have a gutter-based drainage system. The participation of all stakeholders, including the local administration and the local community, is necessary to optimize the sanitation system in Mataram District. The implementation of regulations and the provision of infrastructure are essential for the support of drainage and waste management systems. To preserve the cleanliness of wastewater channels, the community can take an active role in processing refuse, beginning at the household level and cleaning the gutters.